PENGARUH PEMBERIAN KOMPRES HANGAT REBUSAN AIR SERAI TERHADAP NYERI PADA LANSIA DENGAN RHEUMATOID ARTHRITIS - Nurjannah; Tiara Desta Rahmawati (Jurnal Kesehatan dan Pembangunan, 2024)
Rheumatoid Arthritis is an autoimmune disease or disease that occurs when the body is attacked by the body's own immune system which results in long-term inflammation of the joints which causes inflammation, stiffness, swelling and pain in the joints, ligaments and bones. The aim of this study was to determine the effect of warm compresses boiled with lemongrass water on pain in elderly people with Rheumatoid Arthritis. The research design uses a quasi-experiment (pre-experiment) with a one-group pre test-post test design approach. Sampling used a purposive sampling technique, namely 55 respondents. The research instrument used the Numeric Rating Scale (NRS) pain scale observation sheet. Statistical tests use the Wilcoxon test p value < ( = 0.05). The results of the Wilcoxon test analysis show that the p value = 0.000 < (0.05), meaning that a warm compress with lemongrass boiled water can reduce the pain level of elderly people suffering from rheumatoid arthritis. There is an effect of warm compresses boiled with lemongrass water on pain in elderly people with rheumatoid arthritis. It is hoped that the suggestions will provide education on non-pharmacological treatment to reduce the scale of pain in elderly people suffering from rheumatoid arthritis independently to be carried out at home in addition to pharmacological treatment.